Ttyl - Myracle, Lauren, 1969- (New York : Amulet Books, 2004)
Chronicles, in "instant message" format, the day-to-day experiences, feelings, and plans of three friends, Zoe, Maddie, and Angela, as they begin tenth grade
Keywords: Instant messaging -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction